Analysing the Power of Language in a Political Text - Abdulamir, Suhair Adel (Arab Journal for Sciences and Research Publishing, 2023)
This research tackles the analysis of overstatement as a persuasive tool and one of the manifestations of the power of language in a political text. It aims at: 1.Demonstrating the concept of the power of language and the common theories related to it.2.Demonstrating the concept of persuasion as an effective tool in language power. 3.Illuminating the effect of overstatements, as a kind of persuasion, on the audience to accept or reject certain opinions or strategies.The researcher has chosen a political speech delivered in front of the US Congress on March 16, 2022 by the Ukrainian President Volodymyr Zelensky, which is taken as a sample. The procedure followed in this research was reading and writing down the overstated sentences used by the Ukrainian President and illuminating their powerful effect in persuasion. The President presented his issue in an exaggerated way to get the desired effect on Congress to obtain their support in his war against Russia, using some Stylistic ways as superlative degree of comparison of adjectives, metaphor, and hyperbolic metaphors.
Keywords: Volodymyr Zelensky; Power of language; Political Text; Persuasion; Overstatement